TRANSFORMASI SPIRITUAL PEMUDA DI MAJELIS MUHIBBURRASUL KOTA PADANG: KAJIAN FENOMENOLOGIS TENTANG PRAKTIK KEAGAMAAN PERKOTAAN - Reo Chandrika; Nelmaya Nelmaya (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study explores the spiritual transformation of youth in the Majelis Muhibburrasul (Muhibbur Rasul) in Padang City using a phenomenological approach, based on the logotherapy theory developed by Viktor Frankl. This study highlights the search for the meaning of life and freedom in existence. This study reveals how youth experience transformation in self-management, the depth of spiritual meaning, and social interaction in the complex urban environment. The findings of this study indicate that participation in the assembly serves as a primary means for youth to find the meaning of life, increase their spiritual awareness, and strengthen their freedom in determining existential attitudes and responsibilities amidst the various challenges faced in the city. These results contribute to theory by emphasizing the importance of the spiritual dimension according to Frankl in religious practices in urban environments.